Biochemical Characterization and Differential Expression of PAL Genes Associated With “Translocated” Peach/Plum Graft-Incompatibility - Amri, Rihab; Font i Forcada, Carolina; Giménez, Rosa; Pina, Ana; Moreno, María Ángeles (Frontiers in Plant Science, 2021)
Grafting is an ancient plant propagation technique widely used in horticultural crops, particularly in fruit trees. However, the involvement of two different species in grafting may lead to lack of affinity and severe disorders between the graft components, known as graft-incompatibility. This complex agronomic trait is traditionally classified into two categories: ‘localized’ (weak graft unions with breaks in cambial and vascular continuity at the graft interface and absence of visual symptoms in scion leaves and shoots) and ‘translocated’ (degeneration of the sieve tubes and phloem companion cells at the graft interface causing translocation problems in neighboring tissues, and reddening/yellowing of scion leaves). Over the decades, more attention has been given to the different mechanisms underlying the ‘localized’ type of graft-incompatibility; whereas the phenylpropanoid-derived compounds and the differential gene expression associated with the ‘translocated’ graft-incompatibility remain unstudied. Therefore, the aim of this study was to shed light on the biochemical and molecular mechanisms involved in the typical ‘translocated’ graft-incompatibility of peach/plum graft-combinations. In this study, the ‘Summergrand’ (SG) nectarine cultivar was budded on two plum rootstocks: ‘Adara’ and ‘Damas GF 1869’. ‘Translocated’ symptoms of incompatibility were shown and biochemically characterized in the case of ‘SG/Damas GF 1869’ graft-combination, three years after grafting. Non-structural carbohydrates (soluble sugars and starch), phenolic compounds and antioxidant activity, were significantly enhanced in the incompatible graft-combination scion. Similarly, the enzymatic activities of the antioxidant enzyme peroxidase, the phenylalanine lyase-ammonia (PAL) and polyphenol oxidase involved in the phenylpropanoid pathway were significantly affected by the incompatible rootstock ‘Damas GF 1869’, inducing higher activities in the scion than those induced by the compatible rootstock ‘Adara’. In addition, a positive and strong correlation was obtained between total phenol content, antioxidant capacity and the expression of the key genes involved in the phenylpropanoid pathway, PAL1 and PAL2. Regarding the ‘SG/Adara’ graft-combination, there were neither external symptoms of ‘translocated’ incompatibility nor significant differences in the biochemical and molecular parameters between scion and rootstock, proving it to be a compatible combination. The differential expression of PAL genes together with the biochemical factors cited above could be good markers for the ‘translocated’ peach/plum graft-incompatibility.